CagY-Dependent Regulation of Type IV Secretion in Helicobacter pylori Is Associated with Alterations in Integrin Binding - Emma C. Skoog (American Society for Microbiology, 2018)
ABSTRACT Strains of Helicobacter pylori that cause ulcer or gastric cancer typically express a type IV secretion system (T4SS) encoded by the cag pathogenicity island (cagPAI). CagY is an ortholog of VirB10 that, unlike other VirB10 orthologs, has a large middle repeat region (MRR) with extensive repetitive sequence motifs, which undergo CD4+ T cell-dependent recombination during infection of mice. Recombination in the CagY MRR reduces T4SS function, diminishes the host inflammatory response, and enables the bacteria to colonize at a higher density. Since CagY is known to bind human α5β1 integrin, we tested the hypothesis that recombination in the CagY MRR regulates T4SS function by modulating binding to α5β1 integrin. Using a cell-free microfluidic assay, we found that H. pylori binding to α5β1 integrin under shear flow is dependent on the CagY MRR, but independent of the presence of the T4SS pili, which are only formed when H. pylori is in contact with host cells. Similarly, expression of CagY in the absence of other T4SS genes was necessary and sufficient for whole bacterial cell binding to α5β1 integrin. Bacteria with variant cagY alleles that reduced T4SS function showed comparable reduction in binding to α5β1 integrin, although CagY was still expressed on the bacterial surface. We speculate that cagY-dependent modulation of H. pylori T4SS function is mediated by alterations in binding to α5β1 integrin, which in turn regulates the host inflammatory response so as to maximize persistent infection. IMPORTANCE Infection with H. pylori can cause peptic ulcers and is the most important risk factor for gastric cancer, the third most common cause of cancer death worldwide. The major H. pylori virulence factor that determines whether infection causes disease or asymptomatic colonization is the type IV secretion system (T4SS), a sort of molecular syringe that injects bacterial products into gastric epithelial cells and alters host cell physiology. We previously showed that recombination in CagY, an essential T4SS component, modulates the function of the T4SS. Here we found that these recombination events produce parallel changes in specific binding to α5β1 integrin, a host cell receptor that is essential for T4SS-dependent translocation of bacterial effectors. We propose that CagY-dependent binding to α5β1 integrin acts like a molecular rheostat that alters T4SS function and modulates the host immune response to promote persistent infection.